MycoNews 2019: editorials, news, reports, awards, personalia, book news, and correspondence - David L. Hawksworth (IMA Fungus)
Abstract This first instalment of MycoNews includes: an Editorial “Do we need more governance in taxonomy?”; reports of mycological meetings in Poland (18th Congress of European Mycologists), Iran (4th Iranian Mycological Congress) and Chile (1st Chilean Meeting of Mycology (I Encuentro Chileno de Micología); an award to Lynne Boddy; birthday greetings to Gro Gulden, Marja Härkönen, Gregoire Hennebert, Hannes Hertel, and Junta Sugiyama; tributes to the passing of Francisco Calogne, Stanley J. Hughes, and Jos Wessels; news of four mycological books and one on-line work published in 2019; and a special tribute to Stanley Hughes by Kris Pirozynski.